Psychosomatic Manifestations of Gastrostomy in Head and Neck Surgery - Altemir, Francisco Hernández; Montero, Sofía Hernández; Montero, Susana Hernández; Montero, Elena Hernández; Peña, Manuel Moros (IntechOpen, 2011)
None